Challenges in advancing clinician scientist careers in cardiology in South Africa - Meel, R; Sliwa, K; Zühlke, L (SA Heart Journal, 2025)
Clinician scientists (CS) are medically trained professionals with advanced expertise in both clinical practice and biomedical research.(1) Their aim is to develop a complete understanding of disease processes, from molecular mechanisms to clinical manifestations and therapeutics, enabling them to play an important role in advancing translational research.(1)